FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS MUTU HIDUP MASYARAKAT DI PROVINSI JAMBI - Azizah Azizah (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
The quality of human resources can not be separated from the work productivity of human resources such as qualified human resources that can be seen from its productivity (Siregar, 2009). The improvement of the quality of the public will have an impact on their productivity increase.The Data used in this research is the data period 2002-2014 year secondary because of BPS Jambi Province. The model used multiple linear regression analysis. The results of this research show that Based on estimates using OLS, shows the influence of variable index Infant Mortality (IKB), Index Life expectancy (IHH) and Index Literacy (IndeksMH) jointly significant effect on variable index Quality of Life ( IMH) Jambi expressed from the F-count> F-table that is 12.450> 3.86. Similarly, partially from t-count test results can be seen from the value t count larger than t-table. all variables have a significant influence on variables Quality of Life Index (IMH) in Jambi Province. Keyword: Quality of Life Index (IMH), Index Infant Mortality, Life Expectancy Index, Index Literacy (IndeksMH)